Hubungan antara Saat Penanganan Kegawatdaruratan Maternal di Luar atau Saat Jam Kerja dengan Waktu Tanggap di RSUD LA Temmamala Kabupaten Soppeng, Sulawesi Selatan - Fadillah, Fadillah; Hakimi, Mohammad; Siswosudarmo, Risanto; Malinta, Umar (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2017)
Background: The national maternal mortality rate is still high at 228 per 100.000 live births. Three late allegedly related to high maternal mortality rate, are 1)too late for decision making, 2) too late for access service and 3) too late for get treatment at referral health facility. Response time for maternal emergency treatment in the hospital plays an important role, since it affects the final result.Objective: To determine the relationship between the time of obstetric emergency management and response time.Method: This study used cross sectional design with the population of study was obstetric emergency patients. One hundred and forty-five subjects were divided into two group: group treated outside of working hours as exposed groups and groups treated during working hours as control groups. Delay of response time were observed. Data was processed by statistical program using computer. Chi square test and logistic regression analysis were used to perform statistical tests.Result and Discussion: From September 1st 2015 to April 30th 2016, there were 145 cases with obstetric emergency handled. A total 82 cases among 145 (56,6%) received emergency management outside working hours. It was found that the 1st response time was delayed in handling outside work hours compared to handling during working hours (RR 2,22; 95% CI 164-3,00). The same was obtained at 2nd response time (RR 1,39; 95% CI 1,04-1,86) and 3rd response time (RR 1,65; 95% CI 1,14-2,31). Multivariate analysis was found that time of the emergency handling was the most dominant variable that affect all response time [1st response time (OR 12,61; 95% CI 4,82-32,03), 2nd response time (OR 2,17; 95% CI 1,05-4,47), 3rd response time (OR 7,70; 95% CI 1,91-31,10)]. PONEK with midwife on duty also influence 1st response time (OR 3,28; 95% CI 1,21-8,93).Conclusion: Obstetric emergency management outside of work hours increased the occurence of response time delay.Keywords: Time of management, Obstetric emergency, 1st, 2nd and 3rd response time.